DYNAMIC VISCOSITY MEASUREMENTS BY PHOTON-CORRELATION SPECTROSCOPY - Will, Stefan; Leipertz, Alfred (Springer Verlag (Germany), 1995)
It is shown that absolute values for the dynamic viscosity of liquids can be obtained using photon correlation spectroscopy. The technique is based on the measurement of the particle diffusion coefficient of spheres dispersed in a liquid. In the experiments both PMMA and silica particles were used as a seed. This includes the first application of newly industrially produced silica samples for the goal of viscosity measurements. Experiment results are presented for various liquids at ambient conditions, including some alcohols, alkanes, and the refrigerant R123. Most of the data agree quite well with reference values. Requirements for suitable seed particles and possible reasons For deviations from reference data are discussed, Measurements in liquid mixtures indicate the general possibility for the simultaneous determination of dynamic viscosity and molecular diffusion coefficient in a single experiment.
Keywords: PARTICLE DIFFUSION; PHOTON CORRELATION SPECTROSCOPY; R123; VISCOSITY